Freight train air brake models. Issue 1 (2nd January 2023) - Wu, Qing; Cole, Colin; Spiryagin, Maksym; Chang, Chongyi; Wei, Wei; Ursulyak, Lyudmila; Shvets, Angela; Murtaza, Mirza Ahsan; Mirza , Ikram Murtaza; Zhelieznov, Кostiantyn; Mohammadi, Saeed; Serajian, Hossein; et al.
ABSTRACT: This paper is an outcome of an international collaborative research initiative. Researchers from 24 institutions across 12 countries were invited to discuss the state-of-the-art in railway train air brake modelling with an emphasis on freight trains. Discussed models are classified as empirical, fluid dynamics and fluid-empirical dynamics models. Empirical models are widely used, and advanced versions have been used for train dynamics simulations. Fluid dynamics models are better models to study brake system behaviour but are more complex and slower in computation. Fluid-empirical dynamics models combine fluid dynamics brake pipe models and empirical brake valve models. They are a balance of model fidelity and computational speeds. Depending on research objectives, detailed models of brake rigging, friction blocks and wheel-rail adhesion are also available. To spark new ideas and more research in this field, the challenges and research gaps in air brake modelling are discussed.